Pharmaceutical assistance and/or pharmaceutical care applied to deaf users: Scope review (Research, Society and Development, 2024)
Introduction: Deaf people are a population that has historically faced many obstacles in healthcare due to their need for differentiated communication resources; there are different types of sign language for different languages. Objective: To present a mapping of pharmaceutical assistance and/or pharmaceutical care applied to the deaf population; as well as the strategies and/or techniques used in the care process. Methodology: This is a Scope Review with a time frame between 2019 and 2023. Result: Of the 32 articles retrieved, 1 article met the inclusion criteria. Conclusion: No robust records were found on techniques and strategies that provide effective communication with deaf and hearing-impaired users used by pharmaceutical professionals.